MARii and UMP ink MoU to expand technology expertise through new academic programmes - UMP, PNC (2019)
Kuala Lumpur, 18th November - A Memorandum of Understanding (MoU) was signed between Universiti Malaysia Pahang (UMP) and Malaysia Automotive, Robotics and IoT Institute (MARii). The MOU outlined collaborations in research, academic and student exchange programmes and dual degree programmes, and would also pave the way for the establishment of smart partnerships in knowledge sharing between the two parties.